2012
DOI: 10.17221/6315-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a rumen-protected form of methionine and a methionine analogue on the lactation performance of dairy cows

Abstract: AbstrAct:The objective the present study was to determine the influence of a supplemental methionine analogue, the isopropyl ester of 2-hydroxy-4-(methylthio)-butanoic acid, commercially available as MetaSmart TM , on lactation performance, particularly milk protein production. The effects of this preparation were compared with those of a rumen-protected form of methionine, marketed as Smartamine TM M. Experiments were conducted according to a 3 × 3 Latin square design and included 30 high-yielding dairy cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
3
0
1
Order By: Relevance
“…In many feeding situations, supplementation of Met has been shown to increase milk protein content (Chen et al, 2011) and/or yield (Čermáková et al, 2012;Osorio et al, 2013) as well as milk fat content (Wang et al, 2010). This has also been confirmed in a recent systemic review of the literature (Robinson, 2010) and meta-analysis (Patton, 2010), and it agrees with our results in which milk protein and fat proportions increased modestly with the MET treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In many feeding situations, supplementation of Met has been shown to increase milk protein content (Chen et al, 2011) and/or yield (Čermáková et al, 2012;Osorio et al, 2013) as well as milk fat content (Wang et al, 2010). This has also been confirmed in a recent systemic review of the literature (Robinson, 2010) and meta-analysis (Patton, 2010), and it agrees with our results in which milk protein and fat proportions increased modestly with the MET treatment.…”
Section: Discussionsupporting
confidence: 92%
“…This has also been confirmed in a recent systemic review of the literature (Robinson, 2010) and meta-analysis (Patton, 2010), and it agrees with our results in which milk protein and fat proportions increased modestly with the MET treatment. Patton (2010) suggests that a slight increase in milk yield can also be expected, and, even though this is consistent with the increases in milk yield reported earlier (Wang et al, 2010;Čermáková et al, 2012;Osorio et al, 2013), it does not agree with the reduction in milk lactose yield, or the tendency for milk yield to decrease with MET, in our study. A study by Robinson et al (2000), to determine effects of a Met oversupply, showed that abomasal Met infusion to increase its intestinal delivery by 34 to 39% markedly reduced animal performance.…”
Section: Discussioncontrasting
confidence: 87%
“…Addition of fat increased the ECM yield compared to CON; however, there was no significant difference, probably due to the low number of animals used. Adding HMBi to the diet resulted in the numerical highest ECM yield, both in the production trial and in the present study, as also observed by Phipps et al (2010) and Cermáková et al (2012). However, the effect of HMBi supplementation was only +0.7 kg ECM/d in the production trial (Alstrup et al, 2015) compared to +3.2 kg ECM/d in the present experiment.…”
Section: Feed Intake and Milk Productionsupporting
confidence: 82%
“…The results of the present experiment also showed that supplementing HMBi at 12 or 24 g d −1 did not affect the plasma concentrations of total protein, albumin, glucose, total cholesterol, triglyceride, urea, uric acid, and creatinine ( Table 5 ). The results were in agreement with Čermáková et al [ 31 ] who reported that supplementing HMBi at 0.16% DM did not affect the plasma concentrations of total protein and urea in dairy cows fed a diet based on alfalfa, corn silages, and ensiled corn cobs. However, Han et al [ 14 ] reported that supplementing HMBi at 25 g d −1 increased the serum concentrations of total protein and albumin and decreased the serum concentration of urea in steers fed a diet based on corn silage and corn.…”
Section: Resultssupporting
confidence: 92%